2016
DOI: 10.5650/jos.ess16001
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Composition and Antibacterial Activity of <i>Aristolochia longa</i> L. and <i>Bryonia dioïca</i> Jacq. Growing Wild in Tunisia

Abstract: International audienceThe composition of the fatty acids of the roots and aerial parts of Aritolochia longa (Aristolacheae) and Bryonia dioica (Cucurbutaceae) was analyzed by gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS). The oils extracted from the aerial parts of both species were rich in polyunsaturated fatty acids with the essential linolenic and linoleic acids being the most prominent compounds. Oleic and linoleic acids were the majors fatty acids in the roots of both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…No research has been conducted as to the antimicrobial activity of the P. glabra and P. syriaca oils in Iran and other countries so far. However, some experiments have been accomplished about the antibacterial effect of other seed oils and reveal the antibacterial activity of them (Dhouioui et al, ; Huang, Xue, He, & Zhao, ; Karimi et al, ; Shukla et al, ). The antibacterial activity of the P. glabra and P. syriaca oils was tested against five gram‐positive and two gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No research has been conducted as to the antimicrobial activity of the P. glabra and P. syriaca oils in Iran and other countries so far. However, some experiments have been accomplished about the antibacterial effect of other seed oils and reveal the antibacterial activity of them (Dhouioui et al, ; Huang, Xue, He, & Zhao, ; Karimi et al, ; Shukla et al, ). The antibacterial activity of the P. glabra and P. syriaca oils was tested against five gram‐positive and two gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to introduce new sources of the oils or utilize agro‐industrial by‐products as a source of oils, which can be good sources not only essential fatty acids but also of minor bioactive compounds such as tocopherols, sterols, carotenoids (Górnaś, ; Górnaś, Mišina, Lāce, Lācis, & Segliņa, ; Górnaś & Rudzińska, ; Górnaś, Siger, & Segliņa, ; Górnaś, Soliven, & Segliņa, ; Hazrati, Nicola, Khurizadeh, Alirezalu, & Mohammadi, ). These oils could improve the human health and reduce the chronic diseases such as hyperlipidemia, arrhythmia, rheumatoid arthritis, cancer, inflammatory, and autoimmune (Dhouioui et al, ; Ramadan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of A indica against E coli was measured 8 mm and did not exceed the antibacterial effect of ABRET having a zone diameter of 11.1 mm. As a result of the antibacterial test of methanol extract of A longa root grown in Tunisia, 8.50 mm against E coli and 9.83 mm zone diameter against S aureus were measured . A zone diameter of ABRME against E coli and S aureus was measured as 7.5 and 10.1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of various studies of the species, the use of therapeutic properties of roots and leaves researched and explained . Aristolochia longa L. is used in the treatment of sclerosis, nasal cancer, and uterine tumors when used as a whole in alternative medicine, and its root has tangential reducing, non‐toxic, and pain relief properties . Aristolochia ringens Vahl.…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, the polar extracts do not show antimicrobial activity, which contrasts with the activity shown by the non-polar extracts obtained using nhexane and dichloromethane. Dhouioui et al (2016) reported the antimicrobial activity of several fatty acids, including palmitic and stearic acids (also present in Stevia), found in non-polar extracts of aerial parts and roots of Aristolochia longa and Bryonia dioica; these acids showed antibacterial activity against E. coli and Enterococcus faecium. Tadhani and Subhash (2006) reported the antimicrobial activity of non-polar extracts of S. rebaudiana leaves against S. aureus and P. aeruginosa; their findings coincide with those reported in the present work.…”
Section: Resultsmentioning
confidence: 99%